Determining the awareness and knowledge of officers towards ship energy efficiency measures - Beşikçi, Elif Bal (Array, 2021)
Improving energy efficiency practices on ships is crucial for both economic and environmental purposes. Both technical and operational applications are made to increase energy efficiency on ships. The success of energy efficiency applications on ships depends on the effective work of seafarers. Therefore, awareness and knowledge about the energy efficiency of seafarers should be enough. The aim of the study is to determine the awareness and knowledge level of seafarers on energy efficiency on ships and to evaluate energy efficiency practices in maritime transportation companies from the perception of seafarers. In the study, the survey method was used. As a result of the survey, it was found that the knowledge level of the seafarers on ship energy efficiency was low, almost half of them did not receive energy efficiency training but they were informed about the importance of the issue. At the end of the study, it was evaluated that the awareness and knowledge level of officers should be increased in order to improve energy efficiency on ships and suggestions on this issue were determined.